Comparative characteristics of various options for local anesthesia in patients with high intraocular pressure - Bektemirova N.T; Alimov A.B (Genius Publishing Group, 2023)
The purpose of the study is a comparative study of the analgesic effect of various local anesthetics in ophthalmic surgery and their effect on intraocular pressure, intraocular hydrodynamics and relaxation of the ocular muscles.
Keywords: Local Anesthesia; Intraocular Pressure